Integrating district cooling systems in Locally Integrated Energy Sectors through Total Site Heat Integration. (15th December 2016) - Liew, Peng Yen; Walmsley, Timothy Gordon; Wan Alwi, Sharifah Rafidah; Abdul Manan, Zainuddin; Klemeš, Jiří Jaromír; Varbanov, Petar Sabev
Graphical abstract: Highlights: Heat integration of district cooling and chilled water network in industrial clusters for low-grade heat utilisation. An improved methodology is introduced to incorporate Absorption Chillers and/or Electric Chillers in industrial clusters. Simultaneous reduction in fossil fuel-based chilling system in urban area and industrial waste heat venting. General equations for annualized operating and capital cost per unit of chilled water generation are proposed. Six different chilled water generation system configurations are considered in the study. Abstract: Between 20% and 50% of world energy consumption is lost as waste heat through energy conversion and transportation in manufacturing processes. Within industrial clusters and Locally Integrated Energy Systems (LIES), waste heat recovery for the purpose of heating and power generation has been well established via schemes such as process streams Heat Integration, cogeneration system, district heating integration, boiler feed water preheating and Organic Rankine Cycle. Waste heat can also be used to generate cooling energy via technologies such as the absorption chiller. During the summer season and in tropical countries, space cooling in buildings typically consumes up to 50% of the total energy consumption. Further recovery of waste heat to generate cooling can result in huge energy savings and emission reduction. This paper presents a new Total Site Energy Integration concept that integrates not only heat and power, but also cooling. The waste heat technology considered for cooling generation are Absorption Chiller (AC) and Electric Compression Chiller (EC). As there is actually an economic trade-off between amounts of chilled water generated, cooling water and power consumed, the new framework has been proposed to guide users in selecting the most economical waste heat-to-cooling technology for Industrial Clusters and LIES. For the presented case study, the lowest-cost solution used a waste-heat driven AC supplying 4.0 MW of Chilled Water (ChW) and a supplementary EC supplying the remaining 1.0 MW. The electricity demand of the integrated system is loaded by 1.3 MWe through this ChW generation system configuration, while the cooling tower load is increased by 3.3 MW. The ChW is expected to be generated at USD 115.10/kW y compared to USD 270.9/kW y for generating ChW by a conventional EC system without waste heat recovery.